The financial and environmental needs and problems of a group of students with impairments in higher education - Crous, Faan (University of the Free State, 2007)
English: Many countries worldwide have legislation to prevent discrimination against students with disabilities and to integrate them into the general education system on secondary and tertiary levels. Moreover, the United Nations and the Commonwealth support and protect the rights of people with disabilities. However, despite legislation locally and abroad, it appears that many remaining barriers prevent people with impairments from full participation in their communities. Against this background, a survey was conducted to determine the environmental and financial needs and problems experienced by a selected group of South African students with impairments in higher education. The students with impairments from three institutions of higher education, who were included in this survey, expressed a need for direct financial support relating to special equipment, discounts on textbooks, part-time employment and decreased tuition fees. Furthermore, they had special requirements for parking space, buildings and lecture rooms.

Afrikaans: Baie lande dwarsoor die wêreld het wetgewing om diskriminasie te voorkom ten einde studente met gestremdhede in die gewone onderwysstelsel op sekondêre en tersiêre vlak te integreer. Nie net individuele lande nie, maar ook die Verenigde Nasies en die Statebond ondersteun en beskerm die regte van mense met gestremdhede. Ondanks hierdie wetgewing blyk dit egter dat daar steeds baie hindernisse bestaan wat voorkom dat persone met gestremdhede ten volle by hulle gemeenskappe inskakel. Dit is teen hierdie agtergrond dat hierdie ondersoek gedoen is om te bepaal watter finansiële en omgewingsprobleme ’n geselekteerde groep Suid-Afrikaanse studente met gestremdhede in hoër onderwys ervaar. Studente met gestremdhede aan drie inrigtings vir hoër onderwys wat by die ondersoek betrokke was, het ’n behoefte uitgespreek aan direkte finansiële ondersteuning rakende spesiale toerusting, deeltydse werk, verminderde studiegeld en afslag op handboeke. Hulle het ook spesiale behoeftes ten opsigte van parkering, geboue en lesinglokale.
Keywords: Students with disabilities; Discrimination against students with disabilities; Secondary education; Tertiary education; Impairments in higher education